A systematic review on interventions for children with dyslexia - Lim Wai Wai; Yeo Kee Jiar; Lina Handayani (Institute of Advanced Engineering and Science, 2023)
Dyslexia is often described as the most common learning disability among the students that affect their ability to read and write. Children with dyslexia persist to their reading difficulties into adolescence and adulthood if without effective intervention and instruction. Therefore, this paper aims to review on the current state of available interventions for children with dyslexia in Malaysia and compare the interventions conducted outside Malaysia instead of to identify the frequently used for assistive technology tools in improving literacy skills. A total of 30 articles published between 2009 and 2021 that met the inclusive criteria were downloaded from electronic databases such as Scopus, SpringerLink and ScienceDirect. The interventions were divided into two categories which are phonological-based and assistive technology-based. The findings indicated that most of the interventions are focused on assistive technology tools and mobile learning applications become the favorite choice in Malaysia to assist students with dyslexia in ameliorating their learning difficulties. However, the developed mobile learning applications are not focused on teaching phonics and combined all three language skills (reading, spelling, and writing) in an application. Hence, it is imperative that researchers in Malaysia take into account to develop more mobile learning applications that focus on English language phonics and encompass three language skills (reading, spelling and writing) in an application for students with dyslexia.